PENGARUH TURBULENSI AIR TERHADAP WAKTU PEMULIHAN Holothuria edulis DENGAN SKALA LABORATORIUM - Mohamad Gazali (JURNAL PERIKANAN TROPIS, 2015)
Holothuroidea as known as sea cucumber is member of the echinoderm which had important economical value due to highly nutrition and protein compound hance the cultivation has been the profitable bussiness in the following days. However, the transport mechanism became turbulent in the pole water and would affect the organism contain in the preliminary study was conducted to identify the adaptation behavior Holothuria edulis affected by the turbulence effect in laboratory scale. This mini research was aimed to assess tentacles anymore and became default size. Turbulence stress was designed on various interval namely 1, 2, 4, 16 and 32 minutes and each interval was repeated three times. The results analysed by ANOVA and Duncan  post hoc test shown that there was able the variation and significant difference on each recovery time due to various turbulent stress trigging. Analysis of regression also shown high correlation relatively between these two parameters (R=0.784 ; α = 0.95). in order to predict maximum time closely same and more than two hours represented that it  had no longer life or called lethal time. The maximum tolerant time of turbulence was predicted for 19,46 hours by equation y = 6,04x +146.9 second. In conclucion, the  longer of stress time conducted the longer periods H. edulis need to recover to default size and to perform its metabolism.